2022
DOI: 10.1186/s12711-022-00726-6
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive study on size and definition of the core group in the proven and young algorithm for single-step GBLUP

Abstract: Background The algorithm for proven and young (APY) has been suggested as a solution for recursively computing a sparse representation for the inverse of a large genomic relationship matrix (G). In APY, a subset of genotyped individuals is used as the core and the remaining genotyped individuals are used as noncore. Size and definition of the core are relevant research subjects for the application of APY, especially given the ever-increasing number of genotyped individuals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…In a recent study (Abdollahi-Arpanahi et al 2022), accuracies by predictivity and Method LR (Legarra and Reverter 2018) considered resistant to selection bias were nearly identical, which indicates that selection biases with the predictivity formula are low with widespread genotyping. The formulas for the genetic correlations could possibly be incorporated into the LR method to take advantage of simpler computing and better statistics.…”
Section: Discussionmentioning
confidence: 94%
“…In a recent study (Abdollahi-Arpanahi et al 2022), accuracies by predictivity and Method LR (Legarra and Reverter 2018) considered resistant to selection bias were nearly identical, which indicates that selection biases with the predictivity formula are low with widespread genotyping. The formulas for the genetic correlations could possibly be incorporated into the LR method to take advantage of simpler computing and better statistics.…”
Section: Discussionmentioning
confidence: 94%
“…Since the number of core animals is usually smaller than the number of all genotyped individuals, the APY strategy not only reduces the complexity of inverse computation significantly, but also helps to increase the sparsity of the coefficient matrix; thus, it should be beneficial for both computational efficiency and memory usage. Nevertheless, how to select the core animals and how large the number of core animals should be to obtain unbiased results are not that easy to determine for a non-expert or non-experienced beginner ( 32 ). On the other hand, recent research concluded that to ensure reliable estimation of variance components, it is required to consider a core size that corresponds to the number of the largest eigenvalues that explain ∼98% of the total variation in GRM.…”
Section: Methodsmentioning
confidence: 99%
“…The single-step genomic best linear unbiased prediction ( ssGBLUP ) has been successfully implemented in the routine genetic evaluation of several livestock species (Lourenco et al, 2015; Tsuruta et al, 2021; Abdollahi-Arpanahi et al, 2022). The vast adoption of ssGBLUP is associated with the straightforward, simultaneous evaluation of populations composed of genotyped and non-genotyped animals, the non-requirement of pseudo phenotypes, the decrease in biases attributed to double counting and genomic preselection, and reliable estimation of breeding values for complex genetic models (Misztal et al, 2020).…”
Section: Introductionmentioning
confidence: 99%